ONLINE BEHAVIOURAL INTENTIONS: AN EMPIRICAL INVESTIGATION OF ANTECEDENTS AND MODERATORS - Setiowati, Rini; Dermawan, Natalia (Bina Nusantara University, 2010)
The objectives of this paper is to recognize, confirm and evaluate the underlying factors toward behavior intention of Indonesian online shoppers; specifically the antecedents including perceived online reputation, banner advertising, perceived online security, perceived reliability, appearance, site design, and website presentational consistency. Questionnaires were posted through online survey targeted to 200 respondents. The data collection methods and variable measures were discussed. Zero-order correlation and regression analysis were conducted to evaluate whether the antecedents and moderator have relationships with the online behavior intention. Analyses found that perceived online security was the only antecedent variable that directly and positively associated with behavioral intentions. The study also found that perceived switching costs did not moderate the links between those variables, whereas perceived switching inducements moderated the links between banner advertising and perceived online security to online behavior intentions.